Endocrine and reproductive physiology - White, Bruce Alan; Porterfield, Susan P.; Porterfield, Susan P. (Mosby physiology monograph series., 2013)
Part of the "The Mosby Physiology Monograph Series", this title explains the fundamentals of endocrine physiology in a clear and concise manner. It provides you with a basic understanding of how the endocrine system functions in health and disease.